Journal of Human Sport and Exercise - 2021 - Winter Conferences of Sports Science 2021
DOI: 10.14198/jhse.2021.16.proc3.68
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor movement education in primary school during COVID-19 pandemic in the synthetic perceptions of primary school university training student

Abstract: The problem is the new scenario for the school in the SARS-COVID-19 pandemic era, especially in physical education (PE) because of the extreme difficulty to practice body and physical activity by distance for students 5-11 age. The aim is to detect the opinions of master's degree courses in primary education students to have the complex aspects of contents and objectives of PE in outdoor mode. Through a qualitative survey carried out by submitting specific questionnaires by the Google Modules platform at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…When children have little experience in sports and movement, it is not easy to suggest to others how best to perform a task. Children today move too little, both qualitatively and quantitatively [21]. At school, on the other hand, if there is no PE teacher, PE lessons are not always available except in a piecemeal way by teachers from other disciplines [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When children have little experience in sports and movement, it is not easy to suggest to others how best to perform a task. Children today move too little, both qualitatively and quantitatively [21]. At school, on the other hand, if there is no PE teacher, PE lessons are not always available except in a piecemeal way by teachers from other disciplines [22].…”
Section: Discussionmentioning
confidence: 99%
“…At school, on the other hand, if there is no PE teacher, PE lessons are not always available except in a piecemeal way by teachers from other disciplines [22]. Many such teachers, however, do not feel adequately trained to carry out PE lessons and, therefore, PE requires a specialized figure in the field, i.e., a PE graduate, to better plan and structure the activities that are to be performed [21].…”
Section: Discussionmentioning
confidence: 99%
“…992/2018, approved only by the Chamber of Deputies, while already introducing the innovation of the specialist teacher, presented some problems/criticalities ascribed to the nonconsideration of the organizational-didactic and methodological peculiarities of the primary segment of education, as well as of the teaching discipline and of teacher training, which made it difficult to apply without specific amendments. In summary, the primary school framework and organizationaldidactic practices and methodological choices, common to all disciplines, were not considered [13]. The criticalities referred to in the government bill 992/2018 have been overcome by the current law; the formulation of article 103 has provided in detail the methods of implementing this innovative measure for primary school and is PEDAGOGY therefore imminent application by the Ministry of Education.…”
Section: State Of the Art Of Physical Education Teaching In Italian P...mentioning
confidence: 99%
“…It is useful to start from the motivational cornerstones of the provision for a correct application of the law, which intends: -respond to the emerging and urgent needs of the child population, especially in terms of health and well-being and education for correct and healthy lifestyles; -make the educational offer of schools adequate both in qualitative and quantitative terms; -bring Italy into line with European standards where the figure of the specialist teacher in the primary segment of education is quite widespread; -adequately consider the guidelines of the World Health Organization on the benefits that physical activity brings to the body, its structures, and functions in a bio-psycho-social synthesis. Therefore, the educational characterization of physical education must be related to the scientific foundations of the body, movement, sports, and recreational activity, the latter understood as mediators of learning and vehicles of educational principles [13]. Above all, the health aspects must be developed with the aim of psychophysical wellbeing and education for correct lifestyles.…”
Section: The Desirable Educational Characterization Of Physical Educa...mentioning
confidence: 99%
“…For this reason, during the recovery towards normality, it is even more important to involve the elderly in socializing activities, such as LD. It is also recommended to propose programs that can meet the basic movement needs of the special population, taking into account the new regulations due to the pandemic [26,27]. Several studies have shown that exercise can result in decreased depression status in the elderly [28,29].…”
Section: Introductionmentioning
confidence: 99%